Determinants of Inadequate Antenatal Care Utilization Among Indian Women: Evidence From NFHS-5 Using Andersen’s Behavioural Model - Manoli, Aniket; Manoli, Pragati Aniket; Wali, Abhinandan; Hiremath, Shruti (National Journal of Community Medicine, 2025)
Background: In India, despite major investments in maternal health, the utilization of antenatal care (ANC) is suboptimal. This study explores the predictors of less than adequate ANC among Indian women, guided by Andersen's Behavioral Model. Methods: The study included a nationally representative subsample of 19,089 women from NFHS-5 (2019-21), of whom 13,670 (71.6%) had adequate ANC (≥4 visits) and 5,419 (28.4%) inadequate ANC. Suboptimal ANC was defined as less than 4 pregnancy visits. Associated factors were determined by chi-square tests and multivariable logistic regression. Results: Insufficient ANC coverage was found in 28.4% of the participants. College or university attendance was a strong predictor of adequate care versus none. The use of the poorest quintiles was poorer than that of the richest for women. Urban place of residence was protective as opposed to rural. ANC use was higher in the South than in the North. Long distances to water sources (>30 minutes) were associated with poor care. The main obstacles were distance to the facilities (32.03%), financial difficulties (27.07%), and transportation problems (23.95%). Conclusions: There is enormous inequity in the utilization of ANC along socioeconomic, geographic, and demographic lines in India. Integrated interventions are needed to mitigate supply and demand-side prerequisites for maternal healthcare, focusing on the most socially and geographically excluded to enhance both access to and use of maternal healthcare services.